Case Report: Acute arterial occlusion of the right lower extremity due to left atrial invasion from pulmonary metastases of thyroid cancer - Akabane, Kentaro; Watanabe, Tetsuo; Tajima, Yuta; Toyama, Shuji; Tamate, Yoshihisa; Uchida, Tetsuro (Frontiers in Cardiovascular Medicine, 2023)
Cardiac metastases of thyroid cancer are rare. The most common metastatic route is through lymphatic or hematogenous spread to the right side of the heart. Direct invasion of metastases from other adjacent organs to the left side of the heart is even rarer. In many cases, the disease progresses asymptomatically, and symptoms appear only when it is already fatal. A 68-year-old woman underwent total thyroidectomy and right-side lymph node dissection for papillary thyroid cancer and multiple lung metastases 7 years previously. The patient was referred to our hospital due to sudden pain in the right lower extremity and motor disturbance. Computed tomography revealed acute arterial occlusion of the right lower extremity due to tumor dispersal from a left atrial invasion caused by multiple pulmonary metastases of thyroid cancer, and only emergency thrombectomy was performed. Although blood flow was restored, the patient died of respiratory failure 2 months after the procedure. Radical resection is considered difficult in cases of direct invasion of metastases from other adjacent organs because multiple metastases have often already occurred. Therefore, in the terminal stage, it might be too invasive to resect a tumor only to prevent embolism recurrence. The treatment strategy should depend on the patient's prognosis and choice.